1995
DOI: 10.1007/bf00183696
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren's disease: analysis of 110 patients on a long-term follow-up

Abstract: The analysis of the surgical therapy results of 110 patients suffering from Dupuytren's disease with an average follow-up of seven years is presented. This was done using the Tubiana staging system, the basis of which is carefully explained in the paper. By determining the recurrence rate (46.4%) and the extension rate (19.2%) in 125 operated hands, the importance and the gravity of recurrence in each of the 292 hand rays is emphasized. The influence on recurrence and extension of factors usually associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Hyperextension was included in 11 of the studies [ 11 , 33 , 50 , 53 , 66 , 72 , 75 , 77 , 80 , 83 , 89 ]. The description of how this was recorded and analysed varied between studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hyperextension was included in 11 of the studies [ 11 , 33 , 50 , 53 , 66 , 72 , 75 , 77 , 80 , 83 , 89 ]. The description of how this was recorded and analysed varied between studies.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperextension measurement was included in results in four studies [ 11 , 66 , 77 , 83 ] without prior description in the text or discussion on how hyperextension was analysed. Three studies [ 72 , 75 , 89 ] indicated that hyperextension was included in a composite ROM measure with only one [ 75 ] stating how hyperextension was calculated within the composite measure. One publication clearly described how hyperextension was recorded and analysed as a zero value [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations